The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1371/journal.pone.0092846
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of an Overweight/Obesity Transition among School-Aged Children and Youth in Sub-Saharan Africa: A Systematic Review

Abstract: BackgroundPrevalence of childhood overweight/obesity has increased considerably in recent years. The transition to higher rates of overweight/obesity has been well documented in high income countries; however, consistent or representative data from lower income countries is scarce. It is therefore pertinent to assess if rates of overweight/obesity are also increasing in lower income countries, to inform public health efforts.ObjectiveThis systematic review aimed to investigate the evidence for an overweight/ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
157
6
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(186 citation statements)
references
References 226 publications
19
157
6
4
Order By: Relevance
“…21 A review of 68 studies of overweight/ obesity in school-children in sub-Saharan Africa found evidence of a transition towards increasing overweight/ obesity, but there was no attempt to assess the validity of the BMI recorded in references as indicative of excessive fatness for the children in these studies. 23 Large longitudinal studies are required to show how international growth references do or do not match the growth patterns of children of different nationalities and racial groups, what this means in terms of the proportions and distribution of body fat and lean tissue, and how these relate to later outcomes for children. Simple, non-invasive but reliable methods are also required to determine the amount of fat and its distribution within bodies.…”
Section: Overweight and Racial Differencesmentioning
confidence: 99%
“…21 A review of 68 studies of overweight/ obesity in school-children in sub-Saharan Africa found evidence of a transition towards increasing overweight/ obesity, but there was no attempt to assess the validity of the BMI recorded in references as indicative of excessive fatness for the children in these studies. 23 Large longitudinal studies are required to show how international growth references do or do not match the growth patterns of children of different nationalities and racial groups, what this means in terms of the proportions and distribution of body fat and lean tissue, and how these relate to later outcomes for children. Simple, non-invasive but reliable methods are also required to determine the amount of fat and its distribution within bodies.…”
Section: Overweight and Racial Differencesmentioning
confidence: 99%
“…A study among sub-Saharan African children and youth demonstrated that this increase is similar to that of developed countries [1], while another has indicated a higher relative increase (+65%) in developing countries than developed countries (+48%) [2]. In Cameroon, the numbers of individuals affected is on the rise and also remains a challenge.…”
Section: Introductionmentioning
confidence: 98%
“…1 Many low-and middle-income countries (LMIC) have shown similar or even more rapid increments of childhood obesity compared with highincome countries (HIC). 2,3 Although the increment of obesity in some HIC seems to be leveling off, the prevalence remains very high. 1 Unfortunately, the data for time trends in physical activity (PA) and sedentary behaviors among children and adolescents from LMIC are extremely sparse.…”
Section: Introductionmentioning
confidence: 99%